Examining the impact of multiple negative online consumer reviews & review helpfulness ratings on persuasion - Neo, Rachel Lijie (2010)
With the phenomenal growth of the Internet, online product information seeking has become a popular activity that forms a key component of the lucrative global e-commerce industry. Increasingly, consumers are relying on online consumer reviews (OCRs) when making purchase decisions. Research has suggested that consumers tend to regard negative OCRs as more important than positive OCRs when evaluating a product. It is thus crucial to examine how web interface cues influence the way people process information from negative OCRs. This study draws upon information processing models to examine the persuasive impact of multiple negative OCRs and the proportion of peer-based ‘helpful’ votes. Findings showed that multiple negative OCRs affected message elaboration but not attitudinal outcomes and behavioral intentions. Also, the proportion of peer-based ‘helpful’ ratings did not have any persuasive impact. Implications of these findings are discussed.